The Influence of Education and Training on Improving Employee Performance Through Work Motivation as an Intervening Variable at the Medan Maimun District Office - Lisniat Tri Putri Halawa; Reza Nurul Ichsan; Yulia Tiara Tanjung (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
In the era of globalization and increasingly fierce competition, every organization is required to improve the performance of its employees in order to achieve the goals that have been set. Organizations/agencies that are established always have the hope that in the future they will experience good development within the scope of the agency and want to create effective performance in their field of work. Low work motivation, whether caused by awards, a less conducive work environment, or limited career development opportunities, can hinder the improvement of employee performance even though they have received training. The formulation of the research problem is 1) How much influence does education have on improving the performance of employees at the Medan Maimun District Office?, 2) How much influence does training have on improving the performance of employees at the Medan Maimun District Office?, 3) How much influence does education have on work motivation at the Medan Maimun District Office?, 4) How much influence does training have on work motivation at the Medan Maimun District Office?, 5) How much influence does work motivation have on improving the performance of employees at the Medan Maimun District Office?, 6) How much influence do education and training have on improving the performance of employees at the Medan Maimun District Office?, 7) How big is the influence of education and training on work motivation in the Medan Maimun Sub-district Office?, 8) How big is the influence of education and training on improving employee performance through work motivation in the Medan Maimun Sub-district Office?. The research method used is quantitative with a sample of 54 people. The results of the study show that education has a positive and significant effect on employee performance in the Medan Maimun Sub-district Office. Training has a positive and significant effect on employee performance in the Medan Maimun Sub-district Office. Education has a positive and significant effect on employee work motivation in the Medan Maimun Sub-district Office. Training has a positive and significant effect on employee work motivation in the Medan Maimun Sub-district Office. Work motivation has a positive and significant effect on employee performance in the Medan Maimun Sub-district Office. Education and training together have a positive and significant effect on employee performance in the Medan Maimun Sub-district Office. Education and training have a positive and significant effect on employee work motivation in the Medan Maimun Sub-district Office. Education and training have a positive and significant effect on employee performance through work motivation as an intervening variable in the Medan Maimun Sub-district Office.